Historia de Nadas - Barba, Andrés, 1975- (Tres edades ;, 2015)
In a peaceful town where nothing ever happens, people are devastated when the stars in the sky suddenly disappear. A team of the town's elite including the obese mayor, a boxer who never fights, and Maderito, a boy made out of wood, embark on a journey to visit three wise men, hoping to find a solution.